Opsoclonus-myoclonus paraneoplastic syndrome in nasopharyngeal carcinoma. Issue 10 (26th October 2022) - Stewart, Kirsten E; Zeidler, Martin; Srinivasan, Devraj; Yeo, Justin C L
Abstract : Nasopharyngeal carcinoma can present with epistaxis, cervical lymphadenopathy, audiological symptoms secondary to eustachian tube dysfunction, pain, or neurological symptoms from tumours directly invading the skull base. It is unusual for patients to present with indirect systemic manifestations. Paraneoplastic neurological syndrome can precede clinically overt malignancy by up to 5 years; therefore, a combination of thorough clinical, laboratory and radiological investigations is required to reach a diagnosis. Intravenous immunoglobulin and steroids might improve neurological symptoms initially and prevent irreversible neuronal damage, but treatment of the underlying cancer is important for long-term resolution. Our case adds to a small but growing body of literature related to anti-Ri antibodies, opsoclonus-myoclonus syndrome presentations, and is the first reported association of this combination with nasopharyngeal carcinoma.